2007
DOI: 10.1124/jpet.106.117101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pan- and Subtype-SelectiveN-Methyl-d-aspartate Receptor Antagonists on Cortical Spreading Depression in the Rat: Therapeutic Potential for Migraine

Abstract: Spreading depression (SD) has long been associated with the underlying pathophysiology of migraine. Evidence that the Nmethyl-D-aspartate (NMDA) glutamate receptor (NMDA-R) is implicated in the generation and propagation of SD has itself been available for more than 15 years. However, to date, there are no reports of NMDA-R antagonists being developed for migraine therapy. In this study, an uncompetitive, pan-NMDA-R blocker, memantine, approved for clinical use, and two antagonists with selectivity for NMDA-R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
106
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 41 publications
(60 reference statements)
10
106
0
Order By: Relevance
“…Memantine, like other NMDA antagonists, has been found to modulate CSD [5]. It is therefore possible that memantine could reduce episodic increases in cortical excitability underlying migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Memantine, like other NMDA antagonists, has been found to modulate CSD [5]. It is therefore possible that memantine could reduce episodic increases in cortical excitability underlying migraine.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, the infusion of Mg 2+ provided sustained headache relief (Bigal et al 2002), and oral Mg 2+ has been demonstrated to be an effective prophylactic in menstrual migraine (Facchinetti et al 1991). Thus, glutamate receptor modulators seem to be of benefit in migraine treatment; indeed, the NMDA receptor antagonist memantine and the NR2B subunit containing antagonist, CP-101,606, decreased spreading depression (Peeters et al 2007), a potentially important factor in migraine pathophysiology. However, stronger basic and clinical evidence for the delineation of their exact role in the pathogenesis of migraine, as well as their cardiovascular safety, is awaited with great interest.…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…23 Moreover, multiple CSDs induced in vivo by continuous K + microdialysis or topical application of a KCl cristal are strongly reduced in frequency but not completely suppressed by P/Q-type (or N-type) Ca 2+ channel blockers 24 and by NMDA antagonists (that also reduce their amplitude and duration). 25,26 The Ca 2+ channel blockers do not affect CSD induced by pinprick in vivo. 24,27 Thus, even limiting our discussion to the methods that are used to elicit CSD in normally metabolizing cortical tissues (because the pharmacological profile of hypoxia and/or ouabain-induced CSD is again different), it is clear that different methods lead to different pharmacological profiles regarding the role of NMDA receptors and Ca 2+ influx through P/Qtype Ca 2+ channels in CSD induction and propagation.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%